Analysis of Implicatures in TikTok User Interactions: A Pragmatic Study of Comments on the Mamanya Kamari Account - Alse Mbatono; Yunidar Yunidar; Julia Marfuah; Syamsuddin Syamsuddin; Ulinsa Ulinsa (Global Education Journal, 2026)
The development of technology in this digital era has made communication more complex and dynamic. This study aims to describe the types and meanings of implications in TikTok user interactions on Mamanya Kamari's account based on a pragmatic study. This study uses a qualitative descriptive method with data in the form of TikTok user comments that contain implications. The data collection technique uses observation, documentation and recording techniques, namely by capturing the screen of the words that are the source of the data, carefully recording the relevant words or sentences from the existing data source. Data analysis techniques use data collection models, data reduction, data presentation, and conclusion drawn. The results of the study showed that 20 implication data were found consisting of 10 conventional implications and 10 conversational implications. Conventional implication is characterized by the use of certain words such as but, but, though, and  even those that directly contain additional meanings in speech. Meanwhile, the implications of the conversation arise based on the context of the situation, the intention of the speaker, and the mutual understanding between the speaker and the reader. The meaning of the implications found includes praise, humor, sarcasm, criticism, and emotional expression. In addition, the use of emojis in comments plays a role in strengthening meaning, expressing emotions, and helping to clarify the meaning of speech. Thus, the implications in TikTok's comments show that digital communication is not only informative, but also expressive and contextual.